Awareness contexts revisited: indeterminacy in initiating discussions at the end‐of‐life. (18th April 2013) - Richards, Naomi; Ingleton, Christine; Gardiner, Clare; Gott, Merryn
Abstract Aims To explore if and how information about a transition to a palliative care approach was communicated to patients recently discharged from hospital and who fulfilled standardized criteria for palliative care need. Background Palliative care philosophy and, more recently, UK palliative care policy, endorse a context of 'open' awareness, where all parties openly acknowledge that the patient's death is approaching. The perceived benefits of making the patient aware of their prognosis encompass a variety of planning activities, which mean that death, when it occurs, is arguably more in keeping with the wishes of the patient. Design A qualitative inductive interview study conducted in 2010–2011. Methods Fifteen semi‐structured interviews were conducted with 15 patients and 3 family carers. All patients were identified as having palliative care needs according to standardized criteria, 3–6 months after discharge from hospital. A thematic analysis was undertaken. Findings Contrary to the professed ideal of 'open' awareness, some participants were only partially aware and others wholly unaware that they were likely to be approaching the end‐of‐life. Those identified as unaware were over 85. Participants displayed a reluctance to acquire knowledge which would require them to face the imminence of death. Conclusion Philosophy and policy aside, people do not always conform to the autonomy paradigm of a self‐directed life followed by a self‐directed death.